First Abundance Estimates of Heaviside’s (Cephalorhynchus heavisidii) and Dusky (Lagenorhynchus obscurus) Dolphins Off Namibia Using a Novel Visual and Acoustic Line Transect Survey - Martin, Morgan Jennifer; Gridley, Tess; Roux, Jean-Paul; Elwen, Simon Harvey (Frontiers in Marine Science, 2020)
Knowledge of a population’s abundance is of primary importance for conservation management. However, robust estimates of abundance are often difficult to obtain, especially for cetaceans which spend most of their lives submerged. Cetacean abundance is commonly estimated using aerial or vessel-based line transect surveys and distance sampling methods. During 2012–2014, the first line transect surveys to estimate cetacean abundance were conducted in Namibian waters. Surveys took place in the Namibian Islands’ Marine Protected Area (NIMPA), a large MPA located along the southern Namibian coastline. A combined visual and acoustic double-platform survey configuration was used to investigate the factors affecting detectability of the endemic Heaviside’s dolphin (Cephalorhynchus heavisidii) and dusky dolphin (Lagenorhynchus obscurus obscurus). The present analysis estimates the probability of detection on the transect line (g(0)) for these two species and generates density and abundance estimates which incorporate a correction for both animals missed on the transect line and attractive responsive movement. The average annual baseline density and abundance estimates for Heaviside’s dolphins in the NIMPA region during 2012–2014 were 0.08 individuals/km2 (CV = 28.6%, 95% CI = 0.04–0.15 individuals/km2) and 1594 individuals (CV = 28.6%, 95% CI =776–3275), respectively. The average annual baseline density and abundance estimates for dusky dolphins in the NIMPA region during 2012–2014 were 0.16 individuals/km2 (CV = 26.2%, 95% CI = 0.10–0.28 individuals/km2) and 3493 individuals (CV = 26.2%, 95% CI: 2015–6052), respectively. A discussion on the distribution of Heaviside’s and dusky dolphins is provided for this region where such information are urgently needed. Based on existing knowledge of the species and area, these estimates are regarded as reasonable. They indicate moderate sized populations of animals within the NIMPA and provide an important first baseline on which future estimates can build.